Asymmetric Synthesis of 3,3′-Piperidinoyl Spirooxindoles and Discovery of Stereospecific Cycloadducts as Novel Hedgehog Pathway Modulators - Rehan, Mohammad; Flegel, Jana; Heitkamp, Franziska; Pergomet, Jorgelina L.; Otte, Felix; Strohmann, Carsten; Kumar, Kamal (Synthesis, 2020)
An enantioselective hetero-Diels–Alder reaction of alkylidene oxindoles and 2-aza-3-silyloxy-1,3-butadienes, catalyzed by divalent transition metal complexes with N,N′-dioxide ligands offered an efficient access to natural-product-based 3,3′-piperidinoyl spirooxindole class of small molecules. exo-Cycloadducts formed via stereospecific cycloaddition with Z-olefin displayed potent activity in modulation of hedgehog pathway.
Keywords: asymmetric synthesis; hetero-Diels–Alder reaction; spirooxindoles; natural products; hedgehog inhibitors